2015
DOI: 10.14419/ijbas.v4i3.4697
|View full text |Cite
|
Sign up to set email alerts
|

The causes and implications of obstetric malpractice

Abstract: Obstetrics and Gynaecology (O & G) are among the specialties at high risk of malpractice claims. In particular, obstetric malpractice attracts high incidence of claims as birth injuries are usually serious and devastating. The resulting disabilities and malformation from the injuries tend to be life-long and victims are deprived of years of enjoyment in life, independence and productivity. As these injuries occur on the victims early in life, the costs of medical care are usually enormous. As this imposes str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Similarly, study set in Malaysia also found that increased wrong litigation have been enforcing many physicians to leave subspecialty and even the trauma of being sued caused them to suffer di culties in returning to their work. [13] In the present survey, 20 (83.33%) and 7 (29.17%) of victims declared that they were free of any guilt and imprisonment respectively. Similarly, as evidenced elsewhere in USA, sixty ve percent of malpractice claims were dropped or dismissed [10].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Similarly, study set in Malaysia also found that increased wrong litigation have been enforcing many physicians to leave subspecialty and even the trauma of being sued caused them to suffer di culties in returning to their work. [13] In the present survey, 20 (83.33%) and 7 (29.17%) of victims declared that they were free of any guilt and imprisonment respectively. Similarly, as evidenced elsewhere in USA, sixty ve percent of malpractice claims were dropped or dismissed [10].…”
Section: Discussionmentioning
confidence: 48%
“…Regardless of this, as indicated in many literatures, the most common claims and suits were free of errors and even larger percentage were closed without ne of physicians [11]. This substantial increase in claims and medicolegal litigation against Obstetrics and Gynecology department may result in poor health care provision by imposing fear of litigation among health care professionals, and in turn it may lead to early and inappropriate decisions [12]; In some professionals, it resulted in specialists leaving the subspecialty and in some it caused di culties in returning to their work [13].…”
Section: Introductionmentioning
confidence: 99%